HUBUNGAN FAKTOR SOSIODEMOGRAFI TERHADAP PENCEGAHAN DIARE PADA BALITA DI PUSKESMAS PADANG SELASA PALEMBANG (Program Studi Ilmu Kesehatan STIKES Abdi Nusa Pangkalpinang, 2022)
Diarrhea is the number one cause of death in infants 31.4%, under five 25.2%, and the fourth in all groups 13.2%. In South Sumatra in 2020 the incidence ofdiarrhea was 90,094 and increased in 2021 to 94,653. The purpose of this study was to determine the relationship between sociodemographic factors, namelythe level of knowledge and attitudes of mothers towards efforts to prevent diarrhea in children under five at the Padang Selasa Health Center, Palembang. Thisresearch is a quantitative analytic survey with a cross sectional approach. The population used were all mothers who had toddlers who came to the MTBSPuskesmas Padang Tuesday Palembang, and 40 samples were taken by accidental sampling. The analysis used in this study used the chi-square test todetermine the relationship between sociodemographic factors, namely the level of knowledge and mother's attitude towards efforts to prevent diarrhea intoddlers. From the results of the study there were 40 respondents, it was found that mothers had good knowledge of 67.5%, positive attitudes of mothers were72.5% and mothers who made efforts to prevent diarrhea were 65.0%. Through the results of bivariate analysis using the chi-square statistical test on theknowledge variable, it was found that value = 0.004 means there is a significant relationship between knowledge and efforts to prevent diarrhea by mothers oftoddlers and on the mother's attitude variable value = 0.007 means there is a significant relationship between mother's attitude with efforts to prevent diarrheaby mothers of toddlers.